New Trends in Injection-Based Therapy for Thumb-Base Osteoarthritis: Where Are We and where Are We Going? - Sara Tenti; Sara Cheleschi; Nicola Mondanelli; Stefano Giannotti; Antonella Fioravanti (Frontiers Media S.A., 2021)
Thumb-base osteoarthritis (TBOA) is a common condition, mostly affecting post-menopausal women, often inducing a significant impact on quality of life and hand functionality. Despite its high prevalence and disability, the therapeutic options in TBOA are still limited and few have been investigated. Among the pharmacological strategies for TBOA management, it would be worthwhile to mention the injection-based therapy. Unfortunately, its efficacy is still the subject of debate. Indeed, the 2018 update of the European League Against Rheumatism (EULAR) recommendations for the management of hand osteoarthritis (OA) stated that intra-articular (IA) injections of glucocorticoids should not generally be used, but may be considered in patients with painful interphalangeal joints, without any specific mention to the TBOA localization and to other widely used injections agents, such as hyaluronic acid (HA) and platelet-rich plasma (PRP). Even American College of Rheumatology (ACR) experts conditionally recommended against IA HA injections in patients with TBOA, while they conditionally encouraged IA glucocorticoids. However, the recommendations from international scientific societies don't often reflect the clinical practice of physicians who routinely take care of TBOA patients; indeed, corticosteroid injections are a mainstay of therapy in OA, especially for patients with pain refractory to oral treatments and HA is considered as a safe and effective treatment. The discrepancy with the literature data is due to the great heterogeneity of the clinical trials published in this field: indeed, the studies differ for methodology and protocol design, outcome measures, treatment (different formulations of HA, steroids, PRP, and schedules) and times of follow-up. For these reasons, the current review will provide deep insight into the injection-based therapy for TBOA, with particular attention to the different employed agents, the variety of the schedule treatments, the most common injection techniques, and the obtained results in terms of efficacy and safety. In depth, we will discuss the available literature on corticosteroids and HA injections for TBOA and the emerging role of PRP and other injection agents for this condition. We will consider in our analysis not only randomized controlled trials (RCTs) but also recent pilot or retrospective studies trying to step forward to identify satisfactory management strategies for TBOA.